Leishmaniases of the New World from a historical and global perspective, from the 1930s to the 1960s - Jaime Larry Benchimol (História, Ciências, Saúde: Manguinhos)
Abstract The first autochthonous cases of cutaneous and mucocutaneous leishmaniasis in the Americas were described in 1909, but visceral leishmaniasis only erupted as a public health problem in the region in 1934. Today Brazil is the country with the most cases of American tegumentary leishmaniasis, and alongside India has the highest incidence of visceral leishmaniasis. Knowledge production and efforts to control these diseases have mobilized health professionals, government agencies and institutions, international agencies, and rural and urban populations. My research addresses the exchange and cooperation networks they established, and uncertainties and controversial aspects when notable changes were made in the approach to the New World leishmaniases.